Removal torque of zirconia abutment screws under dry and wet conditions - Nigro,Frederico (2010)
The aim of this study was to verify whether screw abutment lubrication can generate higher preload values compared to non-lubricated screws, a titanium abutment was screwed onto an implant analog and scanned with the Procera System to generate 20 zirconia abutments. MKIII Brånemark implants were clamped to a precision torque device, and the abutments were distributed in dry and wet groups with 10 specimens each. In the wet groups, the inner threads of the implants were filled with artificial saliva. All abutments were fastened with a Torqtite screw under 32 Ncm. Ten detorque measurements were performed per group pushing the reverse button of the Torque controller soon after screw tightening with values registered. The mean detorque values were calculated and compared by a Student's t test (?=0.05). The wet condition presented significantly higher mean detorque than the dry condition (31.5 ± 1.2 versus 27.5 ± 1.5 Ncm, respectively; p=0.0000024). In conclusion, there was always a loss in the initial torque values when the removal torque was measured under both conditions. The wet condition presented higher mean torque than the dry condition. Better preload values were established in the wet group, suggesting that the abutment screw must be lubricated in saliva to avoid further loosening.